Ancient restorations at Hierapolis of Phrygia (Denizli, Turkey): Interdisciplinary research on materials and technologies. (October 2018) - Andreotti, Alessia; Baroni, Sandro; Bonaduce, Ilaria; Bozza, Sara; Cantisani, Emma; Ismaelli, Tommaso; Vettori, Silvia
Abstract: The restoration of architectural monuments constituted a common practice in the ancient Mediterranean world and the use of artificial binders in repairing blocks is attested both by literary sources and archaeological evidence. However, the knowledge on the use of these ancient binders and their components is limited, due to the shortness and indefiniteness of the ancient recipes and the difficulty of obtaining and analyzing samples from blocks that have remained exposed to atmospheric agents and have undergone degradation. The paper focuses on the exceptional context of Hierapolis of Phrygia (Denizli, Turkey), where many ancient binders used in the restoration of Roman Imperial-era buildings (Sanctuary of Apollo, Theatre, North Agora and Ploutonion ) have been identified. Thanks to the good state of conservation of these materials, the paper offers the unique opportunity for studying the role of organic additives used in the ancient bonding mortars and understanding the technologies adopted in the architectural restoration. Several analytical methodologies (Pyrolosis and Gas chromatography coupled with Mass Spectroscopy; X-ray diffractometry and Optical Microscopy) were applied to identify the organic and inorganic components. The mortars sampled in Hierapolis showed the presence of casein, animal glue, beeswax and Pinaceae resin, in agreement with the survived ancient recipes on bonding mortars. However, the archaeometric data revealed the use of complex mixtures, which are also attested by the literary sources. In particular, the use of calcite together with various organic additives appeared to be a common practice. Criteria of selection and use of the different mixtures have been discussed. Highlights: An unique opportunity for studying the role of organic additives in the ancient bonding mortars for restoration intervention; a strongly integrated approach, combining archaeology, study of literary sources and archaeometry, was applied; the use of complex mixtures of organic and inorganic compounds was found.